2015
DOI: 10.1093/rb/rbv015
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic biphasic scaffolds for osteochondral defect repair

Abstract: The osteochondral defects caused by vigorous trauma or physical disease are difficult to be managed. Tissue engineering provides a possible option to regenerate the damaged osteochondral tissues. For osteochondral reconstruction, one intact scaffold should be considered to support the regeneration of both cartilage and subchondral bone. Therefore, the biphasic scaffolds with the mimic structures of osteochondral tissues have been developed to close this chasm. A variety of biomimetic bilayer scaffolds fabricat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 80 publications
0
60
0
Order By: Relevance
“…Therefore, attempts have been made to use cell-based tissue repair techniques to intervene in cartilage defects (Donaldson et al, 2015;Li et al, 2015). Therefore, attempts have been made to use cell-based tissue repair techniques to intervene in cartilage defects (Donaldson et al, 2015;Li et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, attempts have been made to use cell-based tissue repair techniques to intervene in cartilage defects (Donaldson et al, 2015;Li et al, 2015). Therefore, attempts have been made to use cell-based tissue repair techniques to intervene in cartilage defects (Donaldson et al, 2015;Li et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Articular cartilage has been demonstrated to possess poor regenerative capacity. Therefore, attempts have been made to use cell-based tissue repair techniques to intervene in cartilage defects (Donaldson et al, 2015;Li et al, 2015). The primary obstacle associated with autologous chondrocyte implantation in articular cartilage repair is the loss of the chondrocyte phenotype (Duan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…With the recent technology advancements on scaffold biological functionality, researchers have focused on creating a bioactive scaffold that mimics the native bone extracellular matrix with both osteoconductive and osteoinductive properties . This can be achieved through the incorporation of bioactive moieties, such as polymers, growth factors, or proteins, into or onto the scaffold …”
Section: Introductionmentioning
confidence: 99%
“…Sung et al reported that fast degradation of the scaffold might negatively affect the cell viability and migration into the scaffold in vitro and in vivo [25,26]. Indeed, we examined the LDH activities slightly increased ( Figure 3B) at day 5.…”
Section: Discussionmentioning
confidence: 83%